2020
DOI: 10.1186/s12875-020-01264-0
|View full text |Cite
|
Sign up to set email alerts
|

Social prescribing for individuals with mental health problems: a qualitative study of barriers and enablers experienced by general practitioners

Abstract: Background There is growing evidence for the use of social prescribing as a means to improve the mental health of patients. However, there are gaps in understanding the barriers and enablers faced by General Practitioners (GPs) when engaging in social prescribing for patients with mental health problems. Methods This study uses a qualitative approach involving one-to-one interviews with GPs from across the UK. The COM-B model was used to elucidate barriers and enablers, and the Theoretical Domains Framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 36 publications
3
44
0
Order By: Relevance
“…The GPs found it challenging to keep up with all new activities and groups in their patients´ local community, which is consistent to the findings by Aughterson et al. (2020). According to the GPs in the study, PA‐counselling seems to lack specific referral advice on PA, which is in line with other studies that show that GPs need signposting opportunities (Carstairs et al., 2020; Jørgensen et al., 2012).…”
Section: Discussionsupporting
confidence: 90%
“…The GPs found it challenging to keep up with all new activities and groups in their patients´ local community, which is consistent to the findings by Aughterson et al. (2020). According to the GPs in the study, PA‐counselling seems to lack specific referral advice on PA, which is in line with other studies that show that GPs need signposting opportunities (Carstairs et al., 2020; Jørgensen et al., 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Qualitative evaluations of social prescribing programmes suggested that there is variation in the level of GP commitment and this can affect implementation. 29,30 Our follow up rate of 57% was lower than other trials, [9][10][11] but this could potentially be improved with reminders by post and phone.…”
Section: Discussionmentioning
confidence: 64%
“…With the increased popularity in community-based or the social prescribing of nature-based activities, there is increased demand for services from the VCSE sector and, thus, a strain on funding and resources [ 47 ]. Financial and practical support are needed to ensure the effective delivery of activities and access for people from different socio-economic and ethnic groups [ 48 , 49 ]. Thus, evidence for the effectiveness of these types of programmes is essential.…”
Section: Introductionmentioning
confidence: 99%